IMPLEMENTASI PRAKTIK PENGALAMAN LAPANGAN (PPL) MAHASISWA UNIVERSITAS PGRI SUMENEP DI SDIT AL-WATHONIYAH - Aprilia Sri Indah Sari; Ike Yuli Mestika Dewi; Farella Ramadhani; Dwi Yunita Putri; Wulansari Wulansari; Nuril Ifki; Fikri Ardiansyah Putra (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Field Experience Practice (PPL) is an important program in prospective teacher education which aims to provide real experience in the world of education. This research aims to describe and analyze the implementation of PPL for PGRI University Sumenep students at SDIT Al-Wathoniyah. The method used is qualitative with a type of field research. Data collection techniques include observation, interviews and documentation. The research results show that the implementation of PPL is going well through classroom learning activities, the use of creative learning media, and involvement in school activities. The PPL program has a positive impact on increasing student activity and developing students' pedagogical, social and professional competencies.